DEU IN NEWSPAPER! "DID YOU KNOW WHAT IS NATURAL be selfish BEFORE A CHILD OF SEVEN YEARS OF AGE?". - Carla de Almeida Pereira Varandas; João Josué da Silva Filho (Universidade Federal de Santa Catarina, 2008)
The study indicates that only after the seven years of age is that children learn to share and take into consideration the feelings of others. In the present study - if two hypotheses: the first claims to be impossible to convince a child to borrow the toy without using a great argument, the second that human beings "learn" to be generous with time and familiarity with the company.